Realization of Thematic Progression to Achieve Grammatical Cohesion in Students' Final Project Backgrounds - Ever Nicolas; Rudi Hartono (English Education Journal, 2022)
This research aimed to find out how the thematic progression structure is applied in the background of students’ research project proposal and how the thematic progression functions to achieve cohesion in the background of the research project proposal. The objectives of this research were to explain the structure of thematic progression and to explain the function of thematic progression to achieve cohesion in the background of the studies section of students’ final project proposal. This research used a descriptive qualitative approach. Fifteen research project proposals were used as the source of the data. The research findings reveal that a constant theme was the primarily used pattern of thematization to organize the research project proposal background in students’ writings. It concluded that the realization of the constant theme was the most straightforward pattern of thematization applied by the students to organize the final projects. That was not hard because the form of the constant theme was just repeated, replaced, substituted, or changed some non-numeral description into a similar way to a clause. Besides, it was found that the amount of reference, substitution, and conjunction occurs in the text, and Ellipsis did not apply to 15 texts. So both grammatical references and substitutions were achieved in this area through thematic progression. The thematization used by the students was able to achieve grammatical cohesion in their writings